New clerodane diterpenoids from the twigs and leaves of Croton euryphyllus. Issue 6 (15th March 2015) - Pan, Zhenghong; Ning, Desheng; Wu, Xingde; Huang, Sisi; Li, Dianpeng; Lv, Shihong
Graphical abstract